2014
DOI: 10.1111/evo.12495
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Architecture of Inbreeding Depression and the Maintenance of Gametophytic Self‐incompatibility

Abstract: Gametophytic self-incompatibility (GSI) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
49
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 36 publications
(91 reference statements)
13
49
1
1
Order By: Relevance
“…Note that when d p = 0, we recovered the same situation as in isolated populations (Gervais et al. ) for the same deme size. Note also that in contrast to the analytical model, SC mutants can occur in any deme.…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…Note that when d p = 0, we recovered the same situation as in isolated populations (Gervais et al. ) for the same deme size. Note also that in contrast to the analytical model, SC mutants can occur in any deme.…”
Section: Methodssupporting
confidence: 76%
“…Gervais et al. () explicitly modeled the accumulation of partially recessive mildly deleterious mutations and considered inbreeding depression as a dynamic variable rather than a fixed parameter in a single SI population. They showed that allowing inbreeding depression to vary had only a marginal impact on the parameter range under which SI is maintained.…”
mentioning
confidence: 99%
“…Alternatively, variability in the success of self‐ and near‐cross‐pollination could be due to early‐acting inbreeding depression because the former is the most extreme form of inbreeding and the latter likely due to mating by individuals that were already closely related. According to theory, maintenance of a self‐incompatible genetic system is linked with strong inbreeding depression (Gervais, Awad, Roze, Castric, & Billiard, ). A self‐compatible mutant that arises within a self‐incompatible population should spread rapidly as long as the costs of selfing do not exceed the 50% transmission advantage and the benefit of reproductive assurance.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini mungkin disebabkan oleh kontaminasi serbuksari dari bunga lainnya dalam satu pohon, atau terdapat kecocokan berkawin sendiri antar bunga dalam satu tandan yang sangat rendah. Hasil ini menunjukkan bahwa metode tersebut tidak dapat digunakan untuk mengetahui pengaruh perkawinan sendiri, dikarenakan bunga jenis ini tersusun dalam malai dengan pertumbuhan yang acropetal sehingga dimungkinkan kuncup bunga sebelum mekar sudah terkontaminasi serbuk lainnya yang sudah mekar terlebih dahulu (Gervais, Awad, Roze, Castric, & Billiard, 2014). Kapsul yang terbentuk dari penyerbukan buatan sendiri terkendali maupun silang terkendali dapat digunakan untuk menduga indeks ketidakcocokan berkawin sendiri (Index of Self Incompatibility/ISI) yang merupakan rasio terbentuknya buliran biji kedua tipe penyerbukan tersebut (Dafni, 1992;Zapata & Arroyo, 1978).…”
Section: Persen Jadi Kapsulunclassified